Analysis of the Effects of Post-Fermentation Freezing Treatment on the Flavor Characteristics of Beibinghong Ice Wine by HPLC and HS-GC-IMS - Yining Sun; Pengqiang Yuan; Guoliang Liu; Yiming Yang; Nan Shu; Wenpeng Lu (Foods)
This study aimed to investigate the effects of post-fermentation freezing treatment on the flavor characteristics of Beibinghong ice wine. Physicochemical indices, organic acids, volatile compound content, odor activity values (OAVs), and sensory attributes of ice wines subjected to different treatments were systematically analyzed using high-performance liquid chromatography (HPLC), headspace gas chromatography–ion mobility spectrometry (HS-GC-IMS), sensory evaluation, and orthogonal partial least squares discriminant analysis (OPLS-DA). The results demonstrated significant differences in fundamental physicochemical indices between freezing-treated and control samples. The freezing treatment significantly reduced total acid, total sugar, and tannin content, thereby alleviating cloyingly sweet and pungent taste sensations and achieving a more harmonious and balanced flavor profile. Concurrently, alterations in the levels of esters, alcohols, and other volatile compounds were observed, with 10% alcohol-by-volume (ABV) freezing-treated samples exhibiting optimal performance in aromatic complexity (featuring fruity and honey notes) and taste balance. Sensory evaluation further confirmed that freezing treatment enhanced the delicacy and complexity of ice wine aromas. This study demonstrates that post-fermentation freezing treatment effectively optimizes the flavor profile of ice wine, providing a theoretical foundation for refining ice wine production processes.